Effect of Organizational Climate and Achievement Motivation on Teacher Performance - Mustika Adriana; Didik Santoso; Yusuf Hadijaya; Fuad Srinio (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This study aims to determine how big the significant influence of organizational climate and achievement motivation on teacher performance at SMKN 1 Percut Sei Tuan. This research is quantitative research with the type of Causal Comparative Research (ex post facto). The population is the teachers of SMKN 1 Percut Sei Tuan which is the sample in this study consisting of 88 teachers. This research instrument uses a data questionnaire on organizational climate, achievement motivation, and teacher performance. Data analysis was carried out using path analysis. Organizational climate has a significant influence on teacher performance at SMKN Percut Sei Tuan by 87.6%, the better the organizational climate, the higher the teacher's performance. Achievement motivation has a significant influence on teacher performance at SMKN 1 Percut Sei Tuan by 89.2%, the higher the achievement motivation, the higher the teacher's performance. Organizational climate and achievement motivation simultaneously (together) have a significant effect on teacher performance at SMKN 1 Percut Sei Tuan by 90.9%, the better the organizational climate and the higher the achievement motivation, the higher the teacher's performance.